Penerapan Manajemen Kurikulum Di SMP Muhammadiyah 1 Medan - Nia Anjunita Sari Purba; Anggun Adelita; Fahira Silva Dilla Nst; Jesicana Silaban; Elisman Siregar; Santa Murni A Situmorang (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
Curriculum management is very important to study or research to find out how it is implemented in education in Indonesia, especially in junior high and high school level schools. To obtain data that is relevant to the research theme, this research used a qualitative research method with a descriptive type, namely research that describes or describes certain situations based on data obtained in detail according to the problems set out in this research. The research is a case study which aims to analyze the Implementation of Curriculum Management at SMP Muhammadiyah 1 Medan. The results of the research show that the implementation of curriculum management at SMP Muhammadiyah 1 Medan has been carried out in a structured and gradual manner for the students. However, there are still challenges or obstacles in implementing effective learning according to the curriculum for students. This is because subject teachers often forget to create or prepare teaching materials that are in accordance with the curriculum determination for students.